Общинне релігійне життя литовського села у ХХ столітті: питання народної релігійності - Мардоса, Й. (Народна творчість та етнологія, 2011)
The article, based on the field ethnographical material and ethnological researches, reveals the forms of rural community religious life in the 20th century. According to the author, the religious life is expressed in three main forms: 1) rituals performed in the rural community by inhabitants themselves; 2) religious activities of the rural community in which priests take part; 3) collective participation of rural community in the church ceremonies. The article deals with these forms of community religious life, their functions and their place in the life of people, village and parish, as the main structural element оf the church.